Letter to Jane Tolmach from Maribes Brennan, President of the Democratic Women's Forum - Maribes Brennan:::::: (1976)
In an April 30, 1976 letter, the Democratic Women's Forum informed Jane Tolmach that it was enclosing a $50 contribution to support her campaign for the California State Assembly. The letter, signed by President Maribes Brennan, expressed sincere hopes that the donation would assist her election efforts and wished her success in the weeks ahead. The organization's letterhead lists its officers, advisory board, and numerous sponsors, reflecting broad support within Democratic women's leadership circles. The contribution represents an early formal endorsement and financial backing from the Forum for her candidacy in the 36th Assembly District.